Effect of liposomal local therapy on salivary glands in acoustic radiation force impulse imaging in Sjögren's syndrome. Issue 10 (October 2016) - Hofauer, Benedikt; Mansour, Naglaa; Heiser, Clemens; Straßen, Ulrich; Bas, Murat; Knopf, Andreas
Abstract The purpose of this study was to evaluate the utility of acoustic radiation force impulse (ARFI) imaging as a monitoring tool for the effect of a liposomal local therapy in patients with dry mouth symptoms due to primary Sjögren's syndrome (pSS). Fifty patients with pSS, diagnosed according to the American-European Consensus Group (AECG) criteria, were included. Clinical data were collected, and sonographic examination including ARFI imaging of the parotid and submandibular glands was performed. Subjective symptoms were evaluated via visual analogue scales (VAS), and the unstimulated whole salivary flow was measured. After a two-month period of liposomal local therapy, sonographic examination was repeated and both subjective and objective symptoms were re-evaluated. Before local treatment, the mean ARFI value of parotid glands was 2.96 m/s (SD 0.97). Mean ARFI value of the submandibular glands was 2.09 m/s (SD 0.71). After the two-month treatment period, a significant decline of ARFI values in the parotid glands to a value of 2.34 m/s (SD 0.70, p  < 0.001) could be observed. The submandibular glands did not show any significant change. Further, a significant reduction of the subjective sensation of dry mouth symptoms could be observed (p  = 0.0001). With the application of ARFI imaging, a decline in parotid gland stiffness could be observed in patients with primary Sjögren's Syndrome accompanied by a significant improvement of the subjective sensation of dry mouth symptoms. The seromucous submandibular glands did not show any changes compared to the serous parotid glands.